Cultural adaptation, content, and protocol of a feasibility study of school-based “Let’s learn about emotions” intervention for Finnish primary school children - Sourander, A.; Ishikawa, S.; Ståhlberg, T.; Kishida, K.; Mori, Y.; Matsubara, K.; Zhang, X.; Hida, N.; Korpilahti-Leino, T.; Ristkari, T.; Torii, S.; Gilbert, S.; et al. (Frontiers in Psychiatry, 2024)
Introduction Emotional awareness and emotion regulation are crucial for cognitive and socio-emotional development in children. School-based interventions on socio-emotional skills have the potential to prevent these problems and promote well-being of children. The Japanese school-based program, Universal Unified Prevention Program for Diverse Disorders (Up2-D2), has shown preventive effects on mental health of children in Japan. The aims of this protocol paper are to describe the unique process of adapting the Up2-D2 from Eastern to Western context, and to present a feasibility study of the intervention, conducted in Finland. Methods The cultural adaptation process started with the linguistic translation of materials, followed by the modification of language to fit the Finnish context. While the Japanese ideology was saved, some content was adapted to fit Finnish school children. Further modifications were made based on feedback from pupils and teachers. The Finnish version of the program was named “Let’s learn about emotions” and consisted of 12 sessions and targeted 8- to 12-year-old pupils. A teacher education plan was established to assist Finnish teachers with the intervention, including a workshop, teachers’ manual, brief introductory videos, and online support sessions. A feasibility study involving 512 4th graders in the City of Hyvinkää, South of Finland, was conducted. It assessed emotional and behavioral problems, classroom climate, bullying, loneliness, perception of school environment, knowledge of emotional awareness, and program acceptability. Discussion The originality of this study underlies in the East–West adaptation of a cognitive behavioral therapy-based program. If promising feasibility findings are replicated in Finland, it could pave the way for further research on implementing such programs in diverse contexts and cultures, promoting coping skills, awareness, social skills and early prevention of child mental health problems. Ethics The ethical board of the University of Turku gave ethics approval for this research. The educational board of the City of Hyvinkää accepted this study.